Managing in a time of great change - Drucker, Peter F. (Truman Talley Books/Dutton, 1995)
In this collection of essays, management expert Peter Drucker examines such topics as the meaning and message of the Information Age, the implications for business in the reinvention of government, the shifting balance of power between management and labor, the differing kinds of teamwork organizations can choose, the lessons to be learned from the rise and fall and rise again of such giants as IBM and GM, where the most important jobs will be in the coming decades, why data management has become the keystone to management success, the fading boundaries between profit and nonprofit organizations, the question of in-house work versus outsourcing, the relationship between the U.S. and Japan, and the promise and perils of China.--From publisher description